A Randomized Controlled Trial on the Efficacy of Xinnaoning Capsule in the Treatment of CSAP Complicated With Qi Stagnation and Blood Stasis Syndrome - Li, Jing; Zhang, Ping; Zhang, Ying; Wang, Haiyun; Wu, Liqi; Zhao, Junnan; Liu, Yue; Zeng, Wenying; Guo, Renzhen; Mei, Jun; Xu, Fengqin (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aims to explore the efficacy and safety of Xinnaoning Capsule (XNN) in the treatment of patients with chronic stable angina pectoris with Qi stagnation and blood stasis syndrome. Methods: A total of 240 patients with chronic stable angina pectoris with Qi stagnation and blood stasis syndrome that met the inclusion criteria were collected from 8 medical centers across China. The trial treatment period was 14 weeks, consisting of the 2-week lead-in period and the following 12-week double-blind treatment period. The drug used in the lead-in period was XNN Simulator. The experimental group was treated with XNN, while the control group was treated with XNN Simulator. The experiments revealed the efficacy of angina pectoris before and after treatment, the relief of symptom, grading changes in the severity of angina, changes in the number of angina pectoris, and the amount of nitroglycerin taken, and at the same time adverse events were also assessed. Results: Compared with the control group, the total score of angina pectoris, the effective rate of angina pectoris, and the severity of angina pectoris in experimental group were statistically significant (P<0.0001). Furthermore, the comparison of the adverse events and the serious adverse events between the experimental group and the control group suggested that the difference was not statistically significant (P=1.0000) before and after treatments. Conclusion: XNN is safe and effective in treating patients with chronic stable angina pectoris with Qi stagnation and blood stasis syndrome.